Analyzing the Role of Responsiveness, Empathy, Reliability, and Customer Satisfaction on Service Recovery Effectiveness - Herry Windawaty; Endang Yuliasih; Nadia Dwi Irmadiani; Marjuki (Journal Management & Economics Review (JUMPER), 2026)
Service failures are inevitable in service organizations, making effective service recovery an essential strategy for maintaining customer satisfaction and long-term relationships. This study aims to analyze the role of responsiveness, empathy, reliability, and customer satisfaction in influencing service recovery effectiveness. A quantitative research approach was employed using a cross-sectional survey design. Data were collected through structured questionnaires distributed to 210 customers who had experienced service recovery following a service failure. The collected data were analyzed using descriptive statistics, reliability analysis, correlation analysis, and multiple linear regression. The findings indicate that responsiveness, empathy, reliability, and customer satisfaction all have positive and statistically significant effects on service recovery effectiveness. Among these variables, customer satisfaction was identified as the strongest predictor, followed by reliability, responsiveness, and empathy. The regression model explained 74.1% of the variance in service recovery effectiveness, indicating that these variables collectively provide substantial explanatory power. The results suggest that organizations should adopt comprehensive service recovery strategies that combine prompt responses, empathetic communication, reliable service delivery, and continuous efforts to improve customer satisfaction. By integrating these dimensions into service management practices, organizations can strengthen customer trust, enhance loyalty, and improve overall organizational performance. This study contributes to the literature on service recovery by providing empirical evidence regarding the combined influence of service quality dimensions and customer satisfaction on service recovery effectiveness, while also offering practical implications for managers seeking to improve customer relationship management.